Model of finite inhomogeneous cavity chain and approximate methods of its analysis - Ayzatsky, M.I. (Вопросы атомной науки и техники, 2021)
A new approach to the description of an inhomogeneous chain of coupled resonators (inhomogeneous disk waveguides) is proposed. New matrix difference equations based on the technique of coupled integral equations and the decomposition method are obtained. Various approximate approaches have been developed, including the WKB approximation. Запропоновано новий підхід до опису неоднорідного ланцюга зв’язаних резонаторів (неоднорідних діафрагмованих хвилеводів). Отримані нові матричні різницеві рівняння, які засновані на техніці зв'язаних інтегральних рівнянь та методі декомпозиції. Розроблені різні наближені підходи, включаючи наближення WKB. Предложен новый подход к описанию неоднородной цепи связанных резонаторов (неоднородных диафрагмированных волноводов). Получены новые матричные разностные уравнения, основанные на технике связанных интегральных уравнений и методе декомпозиции. Разработаны различные приближенные подходы, включая приближение WKB.